Effectiveness of Interpersonal Communication in Nutrition Education on Iron Supplement Knowledge in Adolescent Girls at SMP Muhammadiyah Maros - Manjilala, Manjilala; Idris, Nurul Hikmawati; Rauf, Suriani; Sirajuddin, Sirajuddin (Media Publikasi Cendekia Indonesia, 2025)
Anemia among adolescent girls is a critical health issue that requires serious attention, as it can trigger a chain of nutritional problems in future generations. Providing iron supplementation tablets to adolescent girls is expected to reduce the incidence of anemia in this population group. This study aimed to assess the knowledge level of adolescent girls before and after receiving nutrition education on the importance of iron supplementation. A quasi-experimental study design was used, specifically a one-group pre-test and post-test design. Participants' knowledge was initially pre-tested using a validated questionnaire adapted from previous studies. The questionnaire had been reviewed and validated by experts in the field of nutrition education to ensure its reliability in measuring knowledge about iron supplementation. Nutrition education was delivered through interpersonal communication for approximately 40–50 minutes. Following the intervention, participants' knowledge was reassessed through a post-test. The study sample consisted of 13 adolescent girls enrolled at Muhammadiyah Junior High School, Maros Regency. Data was collected through interviews, and knowledge assessment was performed using the same validated questionnaire. The results showed a p-value of 0.003 (<0.05), indicating a statistically significant improvement in the knowledge of adolescent girls after receiving the nutrition education intervention. The interpersonal communication approach likely contributed to this improvement by enabling active interaction, immediate feedback, and better engagement with the participants, all of which are essential factors in enhancing information retention.